Bribery as a Form of Corruption: A Juridical Analysis and Judicial Practice - Somomoeljono, Suhardi; Kumar, Saurav (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2026)
This study examines bribery as a specific form of corruption within the Indonesian legal framework, focusing on its juridical aspects and judicial practice. Bribery, as regulated in Law No. 31 of 1999 in conjunction with Law No. 20 of 2001 on the Eradication of Corruption Crimes, constitutes a criminal act that undermines public trust, disrupts governmental integrity, and damages the state’s administrative functions. This research analyzes the legal elements of bribery, the scope of criminal liability, and the procedural mechanisms used in investigating and prosecuting bribery cases. Furthermore, the study reviews selected court decisions to evaluate judicial consistency, sentencing patterns, and the effectiveness of judicial reasoning in achieving deterrence. The findings indicate that, despite the existence of strong legal provisions, challenges remain in terms of proving intent, uncovering hidden transactional networks, and ensuring institutional independence in bribery cases. The study concludes that strengthening legal clarity, enhancing investigative capacity, and improving judicial transparency are crucial to increasing the effectiveness of law enforcement against bribery as a corruption offense.